Implementasi Sistem Informasi Manajemen Keuangan, Pembayaran SPP dan Administrasi Siswa Berbasis Web di Perguruan Kristen Methodist Indonesia Kutalimbaru - Apriandi, Virgiawan Bayu; Darwis Robinson Manalu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Financial administration and SPP (tuition fee) payment management at Perguruan Kristen Methodist Indonesia (PKMI) Kutalimbaru currently face various obstacles when conducted conventionally, such as the risk of recording errors, delays in report preparation, and difficulties in monitoring student arrears. This research aims to design and implement a Web-Based Information System for Financial Management, SPP Payments, and Student Administration. The system development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was built using the PHP programming language with MySQL database management. The result of this research is a functional and integrated web-based application capable of managing student master data, processing SPP payment transactions (both online and offline), managing other student administrative data, and generating financial and arrears reports automatically and in real-time. The implementation of this system is expected to improve efficiency, accuracy, and transparency in the school's financial and administrative management, as well as make it easier for parents to monitor payment histories.